ANALYSIS OF ISLAMIC COMMUNICATION ABOUT OXYMORA CANCEL CULTURE ON VIRTUAL MEDIA IN INDONESIA - Yaqinah, Siti Nurul; Antok, Ishak Hariyanto (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
Several public figures have controversies, so the public responds negatively. On the other hand, an Islamic communication perspective is necessary to analyze this phenomenon. Therefore, this research aimed to uncover the dynamics and oxymora cancel culture in virtual media in Indonesia, especially in the context of Islamic communication. Using a netnography approach, this study analyses various cases involving public figures such as Ahmad Dhani, Luna Maya, Gisel Anastasya, Rizki Billar, Tuan Guru Mizan Qudsiyah, and Panji Gumilang on the YouTube platform. The study results show that cancel culture in Indonesia reflects social complexity, where religious values face modern demands for social justice. On the one hand, cancel culture functions as a social control mechanism to maintain religious norms and public ethics, providing a role for society in correcting behavior that is considered deviant. On the other hand, this phenomenon risks creating an intolerant environment, limiting the space for forgiveness and improvement, and potentially violating the principles of compassion and justice in Islam. This research contributes to a deeper understanding of the role of Islamic communication in responding to the phenomenon of cancel culture, emphasizing the importance of a wise and contextual approach in integrating religious values and the demands of modernity in the digital space.